A study of the dependence of the reflectance of the anti-reflective material Ta2o5 on the wavelength of laser radiation - ghazolin, bassam (Latakia University Journal -Basic Sciences Series, 2023)
The study of the dependence of reflectance of the Ta2O5 antireflection coating with wavelength. Experiments were carried out using spectrophotometer based on a prismatic monochromatic SPM covering the spectral rang 450 – 1000 nm. It can be seen from these results that the reflectance of the antireflection layer of the unirradiated sample is less than 10 % the above mentioned spectral range and decreases as the wavelength decreases. Its value is about 7% at 1060 nm and 1-2% at 532 nm. Irradiation of the si solar cell samples by laser pulses had been found to have an observable effect on the reflectance of their antireflection layer; the effect being dependent on the laser radiation wavelength and the number of pulses. For radiation of wavelength 1060 nm, the reflectance for the sample irradiation by a small number of pulses (l = 1060 nm 1 and 3 pulses) becomes ≈ 12%. Since this small number of pulses causes a small heating of the sample surface, in the increase of reflectance may be a result of some sort of cleaning process of the surface antireflection layer, which in turn causes the observed increase of reflectance. As the number of pulses at this wavelength is increased, the reflectance decreases. This is due to the thermal damage of the surface antireflection layer